Flow patterns and transition criteria in boiling water-cooled packed bed reactors. (September 2018) - Xu, Guangzhan; Zhang, Xiaoning; Sun, Zhongning; Ruan, Jing; He, Bin
Abstract: The flow patterns associated with boiling water-cooled packed bed reactors were investigated via experiments. A bed packed with spheres of different diameters, which were heated by means of electromagnetic induction, was investigated over a range of mass flux values and sphere diameters. Three flow boiling patterns occurred in the packed bed: bubble flow, slug flow, and annular flow. Furthermore, generalized flow pattern maps were plotted in terms of the mass flux versus the vapor quality. The effects of mass flux and sphere diameter on the flow region transition were analyzed, and criteria for transitions between flow patterns were proposed based on certain parameters. These parameters included the Reynolds number, ratio of the glass tube diameter to the sphere diameter, and vapor quality. The results indicated that more than 90% of the data are correctly described by the transition boundary criteria. Highlights: Three flow boiling patterns in the packed bed are found. Generalized flow pattern maps were plotted in terms of mass flux versus vapor quality. The proposed transition criteria demonstrate agreement with the experimental data.